2003
DOI: 10.1038/ncb1069
|View full text |Cite
|
Sign up to set email alerts
|

Hsk1–Dfp1 is required for heterochromatin-mediated cohesion at centromeres

Abstract: Heterochromatin performs a central role in chromosome segregation and stability by promoting cohesion at centromeres. Establishment of both heterochromatin-mediated silencing and cohesion requires passage through S phase, although the mechanism is unknown. Here we demonstrate that Schizosaccharomyces pombe Hsk1 (CDC7), a conserved Dbf4-dependent protein kinase (DDK) that regulates replication initiation, interacts with and phosphorylates the heterochromatin protein 1 (HP1) equivalent Swi6 (ref. 6). Hsk1 and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 30 publications
1
110
0
Order By: Relevance
“…We also identified peptides, albeit few, corresponding to previously described Swi6-associated proteins, such as JmjC protein Epe1 (38, 39), Hsk1-Dfp1 (40,41), and Pcr1 involved in heterochromatic silencing (42). Also detected were peptides representing different subunits of SHREC (Fig.…”
Section: Swi6mentioning
confidence: 85%
“…We also identified peptides, albeit few, corresponding to previously described Swi6-associated proteins, such as JmjC protein Epe1 (38, 39), Hsk1-Dfp1 (40,41), and Pcr1 involved in heterochromatic silencing (42). Also detected were peptides representing different subunits of SHREC (Fig.…”
Section: Swi6mentioning
confidence: 85%
“…Recently, Hsk1-Dfp1-mediated phosphorylation of Swi6 has been shown to be critical for stabilizing the binding of Swi6 to heterochromatin (7). Phosphorylation causes a reduction in the electrophoretic mobility of Swi6 (7).…”
Section: Discussionmentioning
confidence: 99%
“…Further work has shown that the RNAi pathway plays a role in the establishment of heterochromatin but not for its spreading (4). The binding of Swi6 is also regulated through phosphorylation by the Hsk1-Dfp1 complex (7); mutations in the Hsk1-Dfp1 kinase complex reduce the binding of Swi6 to heterochromatin, leading to the loss of silencing, increased chromosomal segregation defects, and chromosomal loss during mitosis (7).…”
mentioning
confidence: 99%
“…W303-derived yeast strains containing the hml::pURA3:: GFP::PEST::NLS were generated from Yex730 (23). The original Yex730 strain was created by cloning the first 55 amino acids of the CLN2 PEST degradation tag onto the carboxy-terminal end of yEGFP (Clontech) (40,48). This construct was transformed into a plasmid to produce the fusion gene URA3promoter::NLS::EGFP::PEST::URA3 terminator.…”
Section: Methodsmentioning
confidence: 99%